The Regulation of Ownership of Agricultural Land Rights that Exceeds the Maximum Limit - Ana Rubiyani; Ahmad Ridwan (Jurnal Akta, 2020)
Land is a form of gift given by God, but human has given brain to think the challenges of live like the land problems, so that the government tries to regulate it properly. The problems in this thesis are: 1) How to regulate ownership of agricultural land rights that exceeds the maximum limit based on Act No. 56 (Prp) of 1960 concerning the Determination of Agricultural Land Areas? 2) How is the action taken by the Land Office towards ownership of agricultural land rights that exceeds the maximum limit? The method used is juridical empirical, with descriptive analytical specifications. The method used in this research is an empirical juridical approach. The results of this study are: (1) The regulation of ownership of agricultural land rights that exceeds the maximum limit is based on Act No. 56 (Prp) of 1960, namely that the provisions regarding land restrictions state that the application for ownership rights as referred to in Article 4 paragraph 1 of Act No. 56 (Prp) 1960 was limited to a maximum land area of 2000 m2. 2) The steps of the Land Office in implementing Act No. 56 (Prp) of 1960, namely the need for a concept of supervision and control over control of land rights, given the various problems that often arise such as in land registration activities.